Educational Factors and Spatial Distribution of Human Capital in Rural Areas in Poland - Klonowska-Matynia, Maria (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The main objective of this article is to prepare a hierarchy and typology of rural areas in Poland showing the level of the human capital indicator and his spatial disparities in the context of educational factors. Selected methods of multivariable objects hierarchy and classification were used in the study. In order to measure the level of human capital in rural areas the linear Indicators ordering has been applied based on the standardized sums method. As a result a relative level indicator of Human Capital has been assigned to each area. As a part of the research analysis will be carried out in spatial dimension. Studies confirm that: generally, the level of human capital on rural areas is low; the diversification of the rural space is relatively strong, the polarization has a dual character (center – periphery), the high quality sphere of education and the availability dominate still in the growth centers, and the radius of diffusion does not go in principle outside the ring suburban zone. The subject of the spatial analysis will be rural areas in Poland, in particular their human capital indicators. GUS BDL, NSP, OKE were the main data source.